The impact of spirituality and social responsibility on organizational citizenship behaviour from the Islamic perspective: empirical investigation of Malaysian businesses - Naail Mohammed Kamil,; Mohamed Sulaiman,; Sugumaran Selladurai,; Nadhira Khalid, (Universiti Kebangsaan Malaysian, 2015)
The phenomenon of organizational citizenship behavior (OCB) emanating from the Western value system has received enormous attention from researchers, however, the model of organizational citizenship behavior from other cross cultural or religious perspectives such as the Islamic perspective, has not been much explored. This empirical study attempts to enrich the understanding of OCB from Islamic management perspective. In view of this, Western OCB framework was studied and further enriched in light of the Islamic heritage (Qur’an and Sunnah, i.e. that Prophetic tradition of Prophet Muhammad, peace be upon him) and established the need for Taqwa serving as antecedent of citizenship behaviors from the Islamic perspective. The survey data used for this empirical research was drawn from 405 Muslim employees in business organizations in Malaysia. Principal component analysis (i.e. PCA using SPSS version 18.0) and confirmatory factor analysis (i.e. CFA using AMOS version 18.0) of the constructs; Islamic spirituality (IS), Islamic social responsibility (ISR) and Organizational citizenship behaviour from Islamic perspective (OCBIP), were conducted. Using structural equation modeling (SEM), good fit indices led to two major findings, thus, ISR influences employees’ OCBIP performance; IS does not. Several implications from the study were discussed.